Thermosensitive ferulic acid-modified chitosan gel coatings loaded with selenium nanoparticles for enhanced grape foliar rainfastness and selenium uptake - Songpo Duan; Xin Ouyang; Yingsheng Liu; Dingyi Shen; Zhiming Li; Sijie Song; Hong Shen (Giant)
Traditional Se (selenium) fertilizers are poorly deposited on crop leaves and are easily washed away by rain; these factors limit plant Se absorption and pose potential environmental risks. To address this issue, a thermosensitive Se nanoparticles gel (CS-FA/BP-SeNPs) based on chitosan-ferulic acid (CS-FA) and β-glycerophosphate (β-BP) was developed to increase rain-washing resistance and Se uptake in grape leaves. The CS-FA derivative was synthesized via an amide reaction between chitosan and ferulic acid(1:2); this derivative demonstrated strong antibacterial and antioxidant activity, effectively dispersing the Se nanoparticles (SeNPs) and preventing their aggregation. β-glycerophosphate neutralized the pH value of the CS-FA/SeNPs solution, significantly increasing the stability of the SeNPs (stable for 30 days). Up to 37 °C, the solution rapidly formed a hydrogel, increasing its viscous modulus by 5.1 times and improving adhesion. Compared with SeNPs alone, CS-FA/BP-SeNPs showed superior spreading, reducing droplet splashing and retraction. In simulated rainfall experiments, the CS-FA/BP-SeNPs gel coating retained 91.1 % of the material on the leaf surface, while the corresponding value for SeNPs was 13.6 %, demonstrating excellent rainfastness in the former. In open-field cultivation trials, grape leaves treated with the CS-FA/BP-SeNPs gel coating presented a 141.3–192.7 % increase in the Se retention rate and a 51.3–62.3 % increase in Se uptake than those with SeNPs alone. Additionally, CS-FA/BP-SeNPs significantly reduced Fusarium oxysporum infection rates, demonstrating potential for use in challenging outdoor environments. This thermosensitive gel coating provides an effective strategy for enhancing nanoselenium utilization on crop leaves through its temperature-responsive properties and strong postgelation adhesion.